English Dictionary. (London : HarperCollins, 1998)
In the light of evidence from the Bank of English, this edition of the popular small dictionary includes a range of new words for the first time, and many existing entries have been updated to reflect changes in the way words are used.
Keywords: English language -- Dictionaries; Languages